Gender Construction in the Perspective of Living Fiqh in Indonesia - Arifah Millati Agustina (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2021)
This article aims to comprehensively explain the uniqueness of the emergence of gender issues in Indonesia and contribute to the development of Islamic law in terms of the discovery of Islamic legal products, and introduce local culture underlying the forming of laws depending on place and era, including gender issues, where western and eastern cultures certainly differ in various sides. Living fiqh on gender is a term for responding to women’s issues through interpretation, considering Indonesia’s local culture. Living fiqh is a term for strengthening Islamic legal products, prioritizing the principle of locality. This study used a qualitative method to respond to the concept of living fiqh in Indonesia. The first step in this research was to explore the genealogy of gender issues in Indonesia compared to the history of gender issues in the West. After that, the differences in the causes of gender issues in Indonesia and the West were classified. Finally, the products of fiqh on gender in Indonesian madzhab were found. In this article, the author argues that the products of fiqh on gender in Indonesia have relations with Indonesian culture. Besides, fiqh on gender in Indonesia emerged from the women activists’ anxiety against discrimination in marriage and rules. Fiqh on Indonesian madhab contributes to minimizing gender inequality that emerged massively after strengthening colonialism and the influence of transnational Islam, changing the interpretation of the scripture and madhab fanaticism.